Installing an ERP System with a methodology based on the principles of goal directed project management (Journal of Information Systems and Technology Management, 2009)
This paper describes a generic methodology to support the process of modelling, adaptation and implementation (MAI) of Enterprise Resource Planning Systems (ERPS) based on the principles of goal directed project management (GDPM). The proposed methodology guides the project manager through specific stages in order to successfully complete the ERPS implementation. The development of the proper MAI methodology is deemed necessary because it will simplify the installation process of ERPS. The goal directed project management method was chosen since it provides a way of focusing all changes towards a predetermined goal. The main stages of the methodology are the promotion and preparation steps, the proposal, the contract, the implementation and the completion. The methodology was applied as a pilot application by a major ERPS development company. Important benefits were the easy and effective guidance for all installation and analysis stages, the faster installation for the ERPS and the control and cost reduction for the installation, in terms of time, manpower, technological equipment and other resources.